Analysis of Agropolitan Area Development in Tinggimoncong Sub-District, Gowa District, South Sulawesi - Rian Alfadillah; Fadillah Putra; Mahir; Luthfia Ayu Dhea (Postgraduate, University of Mataram, 2024)
Assessing the problems of economic growth, urbanization, and development prospects in Tinggimoncong District, Gowa Regency, South Sulawesi, Indonesia, have yet to catch up due to economic growth concentrated in cities. The concept of